2022
DOI: 10.1007/s10461-022-03644-2
|View full text |Cite
|
Sign up to set email alerts
|

“The role of case management in HIV treatment adherence: HPTN 078”

Abstract: Adherence to care and antiretroviral therapy is challenging, especially for people living with HIV (PLWH) with additional co-occurring risk factors. Case management interventions, including motivational interviewing (MI), show promise to improve HIV treatment adherence, but few studies have examined how such interventions are delivered to or experienced by PLWH who have been reengaged in care. We conducted qualitative interviews with six case managers and 110 PLWH exiting from a randomized study (HPTN 078) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It may be that the variables measured were limited, and/or we did not adequately measure the most relevant and important social determinants of health. A paper was recently published which evaluated qualitative data collected during exit interviews with study participants and study case managers in this study which provides greater insight into our main study findings, an in-depth description of the multiple barriers to adherence faced by this largely “out of care” population, as well as a more nuanced understanding of the benefits and challenges of implementing MI into case management [33–35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that the variables measured were limited, and/or we did not adequately measure the most relevant and important social determinants of health. A paper was recently published which evaluated qualitative data collected during exit interviews with study participants and study case managers in this study which provides greater insight into our main study findings, an in-depth description of the multiple barriers to adherence faced by this largely “out of care” population, as well as a more nuanced understanding of the benefits and challenges of implementing MI into case management [33–35].…”
Section: Discussionmentioning
confidence: 99%
“…nuanced understanding of the benefits and challenges of implementing MI into case management [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Functions may include client advocacy, care coordination, needs assessment and case monitoring, community engagement, education, administration activities, psychosocial support, and service navigation [6]. Studies in various settings demonstrated that case management improves care engagement and clinical outcomes and is acceptable to both clients and clinical teams [7][8][9][10][11][12][13]. In one study, most participants who were virally unsuppressed at enrollment spoke positively about their case management experience, highlighting case managers' critical role in providing nonjudgmental services and emotional support [7].…”
Section: Hiv Case Management and Virtual Approachmentioning
confidence: 99%
“…Studies in various settings demonstrated that case management improves care engagement and clinical outcomes and is acceptable to both clients and clinical teams [ 7 – 13 ]. In one study, most participants who were virally unsuppressed at enrollment spoke positively about their case management experience, highlighting case managers’ critical role in providing nonjudgmental services and emotional support [ 7 ].…”
Section: Hiv Case Management and Virtual Approachmentioning
confidence: 99%
“…It is an effective counseling approach that emphasizes partnership between clients and providers by creating an atmosphere of trust and acceptance [ 4 ]. MI has substantial evidence for effectively improving adherence to medications and regular clinic follow-up for multiple conditions [ 5 ] such as alcohol use, tobacco use, HIV, and diabetes in various care settings [ 2 , 6 10 ].…”
Section: Introductionmentioning
confidence: 99%